USER INTERFACE DESIGN AND IMPLEMENTATION OF DNA TESTING TOOLS FOR WHITE SPOT SYNDROME VIRUS (WSSV) ON VANNAMEI SHRIMP. - Mario Surya, Laurensius
The aquaculture industry is one of the major industries in Indonesia. The aquaculture industry consists of various commodities such as shrimp, fish, lobster, and others. Of all the aquaculture product exports, the shrimp industry contributed the highest. This large economic impact has made the aquaculture industry, especially the shrimp commodity, an important industry in Indonesia. The conditions of shrimp farming that are not ideal can cause the shrimp to develop a disease. This disease commonly known as White Spot Syndrome Virus (WSSV) disease. This disease is dangerous because it is contagious and can kill shrimp in a short time (1 to 7 days after physical symptoms appear). Shrimp that die from this disease will have a very low selling price, which is detrimental to shrimp farmers. So far, the problems related to WSSV have been tried to be prevented in various ways, but the majority have a low level of accuracy. Based on these problems, this DNA-based WSSV essay was made. This tool is expected to have a more affordable price compared to similar tools on the market so that it can be used in small ponds in the regions. In addition, the use of test equipment in these areas can minimize the time required to test a sample because it can cut transportation times. This tool is also designed to have better accuracy than using the WSSV visual method of observation or water quality testing. The user interface is an important part of a tool or system. The user interface is a means of interaction between the user and the machine. The user interface must have the appropriate functionality. In addition, the user interface must have a design that is easy to use. A good user interface allows users to use the tool well.